2014
DOI: 10.1074/jbc.m114.559294
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of G Proteins to Reconstituted Monomers and Tetramers of the M2 Muscarinic Receptor

Abstract: Background:The allosteric interaction between agonists and guanylyl nucleotides reports on the interaction between G protein-coupled receptors and G proteins. Results: Such allostery differs in kind between reconstituted monomers and tetramers of the M 2 muscarinic receptor. Conclusion: Monomers and tetramers mediate allostery via different mechanisms. Significance: Only tetramers resemble muscarinic receptors in myocardial membranes in the nature of their sensitivity to guanylyl nucleotides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 67 publications
1
47
0
Order By: Relevance
“…Such results have been interpreted as being consistent with the capacity of the receptor to form dimers in a range of ways via a number of distinct interfaces (McMillin et al, 2011;Hu et al, 2012). Recent studies have suggested that rather than being limited to dimers, muscarinic receptors, including both the M 2 (Redka et al, 2014) and M 3 (Patowary et al, 2013) subtypes, may form and potentially function as tetramers. We therefore initiated studies to address such a possibility for structural organization and assess if previous results (McMillin et al, 2011) would be consistent with such a model.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Such results have been interpreted as being consistent with the capacity of the receptor to form dimers in a range of ways via a number of distinct interfaces (McMillin et al, 2011;Hu et al, 2012). Recent studies have suggested that rather than being limited to dimers, muscarinic receptors, including both the M 2 (Redka et al, 2014) and M 3 (Patowary et al, 2013) subtypes, may form and potentially function as tetramers. We therefore initiated studies to address such a possibility for structural organization and assess if previous results (McMillin et al, 2011) would be consistent with such a model.…”
Section: Resultssupporting
confidence: 58%
“…This may be relevant to the observations both herein and in the studies of McMillin et al (2011) of a clear role for amino acids at the cytoplasmic end of TMD IV, as this is not inherently predicted by the rhombic tetramer models. Organization of other class A GPCRs as tetramers has also been supported by approaches, including reconstitution experiments in artificial lipid bilayers (b 2 -adrenoceptor) (Fung et al, 2009), chemical cross-linking studies (dopamine D 2 ) (Guo et al, 2005), and detailed characterization of ligand binding studies (muscarinic M 2 ) (Park et al, 2002;Redka et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas ARC exhibits lower affinity than IXO or QNB as investigated in the present study, certain partial agonists are not necessarily weaker binders compared with full or inverse agonists (16,24). Nevertheless, there appears to be a correlation between efficacy and the breadth of the dispersion of affinities for agonists of the M 2 receptor (16,20,25). The GaMD simulations provided important insights into the binding mechanism of three studied ligands and GPCR graded activation.…”
Section: Discussionmentioning
confidence: 99%